2016
DOI: 10.1002/2016gl069595
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of eddy dynamics from SMOS sea surface salinity measurements in the Algerian Basin (Mediterranean Sea)

Abstract: The circulation in the Algerian Basin is characterized by the presence of fresh‐core eddies that propagate along the coast or at distances between 100 and 200 km from the coast. Enhancements in the processing of the Soil Moisture and Ocean Salinity (SMOS) data have allowed to produce, for the first time, satellite sea surface salinity (SSS) maps in the Mediterranean Sea that capture the signature of Algerian eddies. SMOS data can be used to track them for long periods of time, especially during winter. SMOS SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…For instance, the number of eddies with radius larger than 80 km (50 km) in the North Atlantic (Mediterranean) is largely overestimated in the satellite‐like products (Figures a and e). It is important to remark that, in some cases, the altimetry can correctly capture individual eddies but that is the least likely scenario and should be confirmed by other independent data sets (e.g., Isern‐Fontanet et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…For instance, the number of eddies with radius larger than 80 km (50 km) in the North Atlantic (Mediterranean) is largely overestimated in the satellite‐like products (Figures a and e). It is important to remark that, in some cases, the altimetry can correctly capture individual eddies but that is the least likely scenario and should be confirmed by other independent data sets (e.g., Isern‐Fontanet et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…Resent state of the art satellite observations of SSS, by NASA's Aquarius/SAC-D satellite [Lagerloef et al, 2008] and ESA's Soil Moisture and Ocean Salinity (SMOS) satellite [Kerr et al, 2010], present an opportunity to complement the existing satellite observations of SST, surface winds, air-sea fluxes, and other variables, to observe the signature of mesoscale eddies. The potential of new satellite measurements to observe mesoscale features and eddies have been demonstrated in a few recent studies [Reul et al, 2014;Umbert et al, 2015;Isern-Fontanet et al, 2016]. Yet extracting such information from medium-resolution and noisy satellite data requires application of selective data analysis tools.…”
Section: Introductionmentioning
confidence: 99%
“…can be written for SSH(Isern-Fontanet et al, 2008) b s (k, z) = n e gkη exp(n 0 kz) within this framework, SST and SSH contain the same information and, once buoyancy and the stream function are15 known at all depths, vertical velocities can be estimated(Lapeyre and Klein, 2006;LaCasce and Mahadevan, 2006;Klein et al, 2009;Isern-Fontanet and Hascoët, 2014) LaCasce and Mahadevan (2006). andIsern-Fontanet et al (2006b) demonstrated, for the first time, that this approach can be used to derive ocean currents from real SST measurements and, later,Isern-Fontanet et al (2016b) that it is also possible to use SSS from SMOS. Moreover, the eSQG approach has shown to provide good results in highly variable areas such as the Alboran Sea(Isern-Fontanet, 2016; Isern-Fontanet et al, 2017b) and for small (∼ 10 20 km) coastal eddies(Isern-Fontanet et al, 2017a…”
mentioning
confidence: 99%